High temperature CO2 sorption with gallium-substituted and promoted hydrotalcites - C. V. Miguel (2014)
Hydrotalcites (HTC) and gallium-substituted hydrotalcites (HTC-10Ga) were prepared by co-precipitation and modified by impregnation with alkali (K and Cs) and alkaline-earth (Sr) metals. The materials were tested and screened for CO2 sorption at 573 K. The results indicate that the modification with potassium greatly enhanced the sorption capacity when compared with the original materials (both HTC and HTC-10Ga). An outstanding sorption capacity (2.01 mmol cm(-3) at 1.08 bar) was obtained for the sample partially substituted with gallium and modified with potassium (HTC-10Ga-20K). Moreover, this material was also submitted to sorption-desorption cycles towards CO2 under low-pressure conditions (< 0.0001-0.15 bar) to assess its use in cyclic operation. An average working capacity of 0.97 mmol cm(-3) and 0.25 mmol cm(-3) was obtained after repeated cycles at 573 K and 473 K, respectively. The sorption kinetics was assessed through uptake measurements, showing two parallel resistances, which were well described by the proposed model.